Evaluation of infrared photography for latent bloodstain visualization and the influence of time. (February 2022) - Winnepenninckx, Astrid; Verhoeven, Elke; Vermeulen, Steve; Bekaert, Bram
Highlights: Infrared light photography detects bloodstains on a large array of materials dependent on material composition and texture. Bloodstains on the majority of selected materials were able to be detected using infrared light photography. Bloodstains on a sub-selection of materials could only be visualized using infrared light photography. Time since blood stain deposition does not seem to have a significant impact up to 1 month. Abstract: The localization of latent blood traces at crime scenes is generally performed using fluorescent stains although infrared light has previously been recognized as an effective localization test for bloodstains as it is a non-destructive and non-contact technique. The goal of this study was to evaluate infrared photography for the detection of latent bloodstains on a large number of objects with different compositions frequently encountered at crime scenes. In this study we show that infrared light photography was able to detect bloodstains deposited on 71.7% of materials while bloodstains on 29.2% of materials could only be detected using infrared photography and not through visual photography. Bloodstain could be detected on most fabrics composed of 100% polyester, 100% cotton and 100% wool or a combination of these fibers with other types of fiber such as nylon or viscose. For other materials such as leather, tiles, wood, bricks, parquet, infrared did not improve the visibility of the bloodstains. Finally, the influence of the time of bloodstain deposition was tested over the period of 1 week and 1 month and did not reveal major differences compared to stains after 24 h drying time suggesting that time has little influence on the ability of infrared light and visual light to detect latent bloodstains.